PENGARUH PUPUK ECOFARMING DAN NPK MUTIARA TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT DI MAIN NURSERY PADA MEDIA GAMBUT - Roy Zansen Pardede; Fathurrahman F (UIR Press, 2024)
This study aimed to evaluate the interaction and primary effects of Ecofarming fertilizer and NPK 16:16:16 on the growth of oil palm seedlings in peat soil within a main nursery setting. The research was conducted over a four-month period, from August to November 2022, at the Experimental Farm of the Faculty of Agriculture, Universitas Islam Riau, located in Pekanbaru City. A Completely Randomized Design (CRD) was employed, featuring two factors. The first factor was the Ecofarming fertilizer, tested at four levels: 0, 2, 4, and 6 ml/l of water. The second factor was the dosage of NPK 16:16:16, also with four levels: 0, 7.5, 15, and 22.5 g/polybag. Key growth parameters measured included plant height, the number of fronds, length of the longest frond, increase in seedling stem diameter, and root volume. The collected data were subject to statistical analysis followed by an HSD test at the 5% significance level. Results indicated that the interaction between Ecofarming fertilizer and NPK 16:16:16 had a significant impact on the root volume of oil palm seedlings, with the optimal combination being Ecofarming fertilizer at 6 ml/l of water and NPK 16:16:16 at 22.5 g/polybag. The Ecofarming fertilizer also showed a significant main effect on plant height, the number of fronds, the length of the longest frond, and the increase in stem diameter, with the best treatment being 6 ml/l of water. Additionally, NPK 16:16:16 significantly affected plant height, frond number, frond length, and stem diameter increase, with the most effective dosage being 22.5 g/polybag.